Study of Canine Babesiosis in Pet and Stray Dogs of Kathmandu Valley - Gautam, A; Regmi, C; Neupane, P; Shah, S; Prasai, TP (Nepalese Veterinary Journal, 2023)
Canine babesiosis is caused by protozoan parasites which is usually transmitted via various species of ticks. The parasites ultimately parasitize the erythrocytes of host body, resulting in fever, anemia, and hemoglobinuria. From June 2021 to September 2021, a cross-sectional study using the purposive sampling method was conducted. A total of 140 samples were collected from dogs and were examined for the presence of Babesia spp. using thin blood smear test stained in Giemsa. Regression analysis was done to compare categorical and outcome variables. The overall prevalence of babesiosis was found to be 14.3%. The result showed significantly higher prevalence of babesiosis in tick infected dogs (p<0.05). Sex, age, type and breed wise prevalence were found to be statistically insignificant (p>0.05). In hematological parameters, RBC, Hb, PCV, and platelets declined significantly in positive cases (p<0.05). In TLC, the changes in the Babesia positive cases were statistically insignificant (p>0.05), whereas in DLC of the infected cases, changes only in neutrophils and lymphocytes were statistically significant (p<0.05). The mean temperature in positive cases was found to be 103.44±0.69. This research intends to add some information on the status of babesiosis inside Kathmandu valley with majorly concluding ticks as major cause of diseases. Tick control is therefore critical in order to reduce the prevalence.